Shoreline change due to global climate change and human activity at the Shandong Peninsula from 2007 to 2020 - Gao, Wei; Du, Jun; Gao, Shan; Xu, Yuanqin; Li, Bing; Wei, Xia; Zhang, Zhuoli; Liu, Jie; Li, Ping (Frontiers in Marine Science, 2023)
In this study, how shoreline change responses to global climate change and human activity at the Shandong Peninsula was quantified by analyzing shoreline locations, inshore erosion/accretion rates, and sandy beach profiles for 2007–2020. During the study period, the total shoreline length decreased from 3345.55 km to 3310.18 km, whereas the natural shoreline decreased by 25.41%. As a dominant shore type, the artificial shoreline increased by 827.89 km. Human activities, such as land reclamation and harbor construction, have caused continuous shoreline advance, resulting in a net land increase of 672.40 km2. However, natural shores (e.g., sandy shore) receded at an average annual rate of −1.0 m due to ongoing erosion. The inshore waters of the Shandong Peninsula were largely sedimentary as erosion occurred only at a few hotspots. Therefore, seaward sediment deposition dominated the erosion/accretion trends of the inshore areas of the peninsula. However, global climate change and human activities have exacerbated the erosion caused by sea level rise. Specifically, the climate change caused absolute sea level rise and increasing frequency of extreme weather events, whereas the human activity dominated the transport and supply of sediment in the coastal zone. In the short term, the shoreline of the Shandong Peninsula continues to advance toward the sea due to the growing artificial shoreline. However, this disrupts the balance between sediment supply and marine energies in the coastal zone, and the system then rebalance itself by eroding unprotected natural shores. In the long term, main shoreline evolution trends depend on global climate change and sea level rise which plays a decisive role in shoreline retreat in the Shandong Peninsula.